Brown Girls Who don’t Need Saving: Social Media and the Role of ‘Possessive Investment’ in The Mindy Project and The Good Wife - Moorti, Sujata (Television for Women, 2016)
This poignant assertionby acclaimed actor Viola Davis, star of the series How to GetAway with Murder (ABC, 2014-), during her Emmy acceptance speechwent viral and becamethe flashpoint for heated discussion about contemporary television’s representational practices. The statement draws attention to questions of taste, what is acknowledgedby the industry and audiences as quality television and the political economy of thecontemporary industry. This moment in television history, with its attendant socialmedia afterlife, captures the key elements I wish to explore in this chapter: represen-tations of women of colour, production practices and viewer responses. As Viola Davisnotes in the quote above, the contemporary US television landscape offers limited rolesfor people of colour. The few shows starring people of colour have become the focus ofintense social media exchanges. In this chapter, I will explore how televisual womenof colour have become a key site from which viewers assert a possessive investmentof racialised identity. By focusing on social media responses, I delineate the ways inwhich viewers invest symbolic and literal ownership over these representations.Through such a multifaceted examination, this essay aims to elaborate how women ofcolour are accommodated within the concept of television for women, a term inter-rogated in this volume. In addition, I illustrate the ideological instability of the term‘women of colour’ and the capaciousness of the concept ‘television for women’.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)